Systemic sclerosis associated pulmonary hypertension: improved survival in the current era. Issue 7 (9th December 2005) - Williams, M H; Das, C; Handler, C E; Akram, M R; Davar, J; Denton, C P; Smith, C J; Black, C M; Coghlan, J G
Abstract : Objectives: To measure survival, haemodynamic function and functional class in patients with systemic sclerosis associated pulmonary arterial hypertension (SSc-PAH) in two treatment eras. Methods: Six year longitudinal study of 92 consecutive patients with SSc-PAH diagnosed by cardiac catheterisation. Data were collected both prospectively and retrospectively. Patients were given basic treatment (diuretics, digoxin, oxygen and warfarin). Where clinically indicated, a prostanoid was used as advanced treatment (historical control group). From 2002, the range of treatments available expanded to include bosentan, which was generally the preferred treatment (current treatment era group). Survival was measured from the date of diagnosis of pulmonary hypertension by cardiac catheterisation. Six minute walking distance and haemodynamic function were measured at the time of diagnosis and at least one month after treatment was started. Results: The historical control group comprised 47 patients, all of whom received basic treatment; 27 of these were also treated with prostanoids. The current treatment era group comprised 45 patients, all of whom received bosentan as preferred treatment. Kaplan–Meier survival in the historical control group was 68% at one year and 47% at two years. Survival in the current treatment era group was 81% and 71% (p  =  0.016) at one and two years, respectively. Pulmonary vascular resistance increased in the historical control group (by 147 dyn·s·cm −5 ), whereas in the current treatment era group, it remained stable over an average of nine months (decrease of 16 dyn·s·cm −5, p < 0.006). Conclusion: Survival of selected patients with SSc-PAH has improved in the current treatment era. In contrast to patients treated historically with basic drugs and prostanoids, patients treated in the current treatment era had improved survival associated with a lack of deterioration in cardiac haemodynamic function.